Technology of dialogical learning as a component of future teachers' professional educatio (Pedagogy of Higher and Secondary Education, 2012)
Morozov V. V. Technology of dialogical learning as a component of future teachers' professional education.The article deals with the technology of dialogical training at universities, based on the principle of role prospect.
Keywords: dialogue; technology of dialogical training; role prospect